The Influence of English on the Kurdish Language and Cultural Identity in the Kurdistan Region of Iraq: A Mixed-Methods Study - Jalal Tahir, Bahra; Nazar Mohamad, Basta; Hussein Mahmood, Nozad (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The increasing dominance of English as a global language has raised concerns about its influence on local languages and cultures, particularly in the Kurdistan Region of Iraq. While English proficiency is often viewed as essential for academic and professional success, its widespread use has led to significant linguistic and cultural shifts and how these linguistic and cultural changes impact English Language Teaching (ELT) practices and educational policies. This study investigates the attitudes of Kurdish university students and instructors toward the English language and its influence on the Kurdish language and cultural identity. Data were gathered utilizing a mixed-methods approach, employing semi-structured interviews and questionnaires, involving 100 students from various academic disciplines and 15 university instructors. Findings indicate that while Kurdish students and educators hold positive attitudes toward English due to its perceived utility in academic and professional contexts, its pervasive use has resulted in increased lexical borrowing and a diminished emphasis on Kurdish language development. The findings reveal disconnect between current ELT classroom practices and policy‑level aspirations for bilingual competence. This shows a clear need for teaching methods that use both languages and for training teachers to apply them. The study underscores the need for balanced language policies that promote bilingual proficiency while safeguarding the Kurdish language as a vital component of cultural identity. These findings highlight the importance of implementing well-planned language policies, fostering cultural awareness, and strengthening the presence of Kurdish in academic and professional settings to ensure linguistic and cultural preservation alongside the benefits of bilingualism.